2020
DOI: 10.1016/j.biopha.2020.110629
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 neutralizing antibody levels are correlated with severity of COVID-19 pneumonia

Abstract: Highlights Neutralizing antibody evaluation helps to assess the risk of re-infection. Some COVID-19 patients may not develop neutralizing antibody after recovery. SARS-CoV-2 neutralizing antibody levels are correlated with COVID-19 disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 25 publications
10
55
0
Order By: Relevance
“…3C and s1 ). Higher antibody titers have been paradoxically associated with disease severity in COVID-19 33 , 34 despite evidence for possible therapeutic effect of early administration of exogenous immunoglobulin 35 . It remains to be determined whether these SARS-CoV-2 specific transcriptional findings represent effective early immunity or are part of the virus-induced dysregulation that seems to drive early disease 8 , 12 , 15 .…”
Section: Resultsmentioning
confidence: 99%
“…3C and s1 ). Higher antibody titers have been paradoxically associated with disease severity in COVID-19 33 , 34 despite evidence for possible therapeutic effect of early administration of exogenous immunoglobulin 35 . It remains to be determined whether these SARS-CoV-2 specific transcriptional findings represent effective early immunity or are part of the virus-induced dysregulation that seems to drive early disease 8 , 12 , 15 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that the duration of protective immunity against common cold coronavirus may last 6 to 12 months 41 although others reported that repeat infections are generally associated with milder symptoms and a lower viral load 26 42 . Single intravenous administration of neutralizing antibodies against the spike protein in outpatients with mild or moderate COVID-19 has been shown to reduce the viral load and reduced length of hospitalization 43 . Furthermore, infection with SARS-CoV-2 and vaccine against the spike protein can protect rhesus macaque from a challenge infection 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al, reported that the NAb titers positively correlated with age and CRP levels and negatively correlated with lymphocyte counts on admission [3]. Additionally, Chen et al reported that the patients with older age, higher CRP and LDH levels and with more profound lung involvement had higher titers of NAbs [21]. In line with this report, our patients with advance stage CT ndings had signi cantly higher NAb titers, and NAb titers positively correlated with NLR, AST, LDH, CK, ferritin, CRP, and INR, and signi cantly yet negatively associated with lymphocyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were performed using Statistical Package for the Social Sciences (SPSS) version 21.0(Armonk, NY, USA). The Kolmogorov-Smirnov test was performed to check the normality of the variables.…”
Section: Discussionmentioning
confidence: 99%